Anionic conjugated polytriazole: direct preparation, aggregation-enhanced emission, and highly efficient Al3+ sensing. Issue 37 (7th September 2016) - Dong, Wenhui; Wu, Haiqiang; Chen, Ming; Shi, Yang; Sun, Jingzhi; Qin, Anjun; Tang, Ben Zhong
Abstract : AEE-active anionic conjugated polytriazole was directly prepared by Cu(i )-catalyzed click polymerization, which could be used to specifically and sensitively detect Al 3+ . Abstract : The anionic polytriazole PI with a weight-average molecular weight of 190 300 was facilely and directly prepared in an excellent yield of 98.1% in 6 h by the well-established Cu(i )-catalyzed click polymerization of 4, 4′-diazido-2, 2′-stilbenedisulfonic acid disodium salt hydrate (1 ) and AIE-active tetraphenylethene (TPE)-containing diyne (2 ) under mild reaction conditions. PI is soluble in high polar solvents, and thermally stable with 5% loss of its weight at temperatures higher than 290 °C. The photo-physical property investigation showed that PI possesses the unique feature of aggregation-enhanced emission (AEE). By taking this feature, PI could be used for the specific detection of aluminum ions with a threshold as low as 31 ppb, which could potentially be used for strict drinking water purity control of the aluminum ion content.